Penerapan Teknologi Augmented Reality untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPS Terpadu Kelas VIII UPTD SMP Negeri 1 Gunungsitoli - Lorenza Mei Lusiana Gulo; Wahyutra Adilman Telaumbanua; Bezisokhi laoli; Arianto Lahagu (Jurnal Tematik, 2025)
This research was motivated by the researcher’s observation during the learning process at UPTD SMP Negeri 1 Gunungsitoli, where there have been obstacles in the learning process, resulting in relatively low student learning outcomes. The objectives of this study are: (1) to examine the implementation of Augmented Reality technology in the Integrated Social Studies subject for Grade VIII at UPTD SMP Negeri 1 Gunungsitoli, and (2) to analyze the students’ learning outcomes in the subject through the implementation of Augmented Reality technology. This study employs Classroom Action Research (CAR). It was conducted in class VIII-G with 32 students serving as both the sample and the population. Based on field data collected by the researcher, the findings are as follows: (1) the teacher observation score in the first cycle reached an average of 65.17%, while in the second cycle it increased to 87.5%. (2) Student activity observation in the first cycle reached an average of 50.89% and increased to 88% in the second cycle. (3) The learning evaluation score in the first cycle was 76.57%, and in the second cycle it improved to 90.88%. The mastery percentage in the first cycle was 46.87%, while in the second cycle it reached 93.75%. It can be concluded that the implementation of Augmented Reality technology enhanced both understanding and student learning outcomes. Thus, applying Augmented Reality technology contributes positively to improving the learning outcomes in the Integrated Social Studies subject for Grade VIII students at UPTD SMP Negeri 1 Gunungsitoli.